A comparative physio-chemical study of steel slag blended cementitious materials in presence of hydroxyethyl methyl cellulose. (1st August 2022) - Xu, Linglin; Yang, Ken; Kang, Wang; Hecker, Andreas; Wu, Kai; Ludwig, H.M.
Highlights: Physical improvement of steel slag cement by HEMC is confirmed and analyzed. Ultra-fine grinding is able to improve reactivity of steel slag remarkably. Calcium ion complexation enhanced the dissolution of SCMs. HEMC leads to a new peak in T 2 pattern of 1 H NMR. Abstract: The applications of steel slag (SS) in the cement industry provide a sustainable solution both for construction materials and industrial solid wastes, but the problem of easily bleeding presents a threat to its later performance and utilization efficiency. This work was designed to improve the water retention of SS blended cement by using hydroxyethyl methyl cellulose (HEMC) and evaluate the physio-chemical properties of the modified SS cement. The interaction mechanism between HEMC and SS blended cement was explored via calorimetry, acoustic and electroacoustic spectrometer, low-field NMR relaxometry, XRD, TG-DSC, as well as fluorescent microscopy. Results show that the water retention of SS blended cement mortar is improved both by ultra-fine grinding and incorporating HEMC, while the water retention rates are prominently increased from 84.87% to 94.35% by 0.1% HEMC. Ultra-fine grinding is able to activate SS and improve water retention ability more efficient compared with the application of HEMC. HEMC does not modify the amount of hydration heat but postpones the occurrence of the exothermic peak. A sudden increase in zeta potential demonstrates the Ca 2+ -adsorption on surfaces of SCM and cement particles. An additional peak commences on the 1 H NMR spectrum of HEMC incorporated cement paste, which reflects the water adsorbed by HEMC, starting to submerge after 500 min via the desorption of water. HEMC affects the SS blended mortar via adsorbing on particles in the paste, capturing water and Ca 2+ around it, thus improving the water retention and retarding the hydrate-polymerization.